Cold Acclimation of Trogoderma granarium Everts Is Tightly Linked to Regulation of Enzyme Activity, Energy Content, and Ion Concentration - Mohammadzadeh, Mozhgan; Izadi, Hamzeh (Frontiers in Physiology, 2018)
In this study, cold hardiness and some physiological characteristics of the Khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae) larvae were investigated under different thermal regimes, i.e. control, cold-acclimated (CA), fluctuating-acclimated (FA) and rapid cold-hardened (RCH). In all the regimes, the larval survival rate decreased with a decrease in temperature. Cold acclimated larvae showed the highest cold hardiness following 24 h exposure at -15 and -20 ºC. Control larvae had the highest glycogen content (34.4 ± 2.3 µg/dry weight). In contrast, cold acclimated larvae had the lowest glycogen content (23.0 ± 1.6 µg/dry weight). Change in trehalose content was reversely proportional to change in glycogen content. The highest myo-inositol and glucose contents were detected in cold acclimated larvae (10.7 ± 0.4 µg/dry weight) and control (0.49 ± 0.03 µg/dry weight), respectively. In control and treated larvae, [Na+] decreased, though [K+] increased, with increasing the exposure time. A shape of the thermal reaction of AMP-depended protein kinase and protein phosphatase 2C followed the same norm, which was different from protein phosphatase 1 and protein phosphatase 2A. Protein phosphatase 2A and 2C showed a complete difference in thermal reaction norms. Indeed, thermal fluctuation caused the highest changes in the activity of the enzymes, whereas the RCH showed the lowest changes in the activity of the enzymes. Our results showed a significant enhancement of larval cold tolerance under CA regime that is related to the high levels of low molecular weight carbohydrates under this regime. Our results showed that among the different thermal regimes tested, the cold acclimated larvae had the lowest supercooling point (about -22 ºC) and the highest cold hardiness following 24 h exposure at -15 and -20 ºC.